Bacterial Composition in Shrimp Paste of Northern Sumatra Related to Flavor and Chemical Properties. (February 2020) - Jamilah, I; Suryanto, D; Priyani, N; Khoiriah, W N; Hartanto, A; Ahmad, F
Abstract: Various bacterial species may be involved in the process of shrimp paste or Terasi fermentation which affects the flavor and aroma of the product. This study investigated the culturable bacterial isolates from each terasi with favored and unfavored taste along with its chemical properties. Four shrimp pastes were collected as representative samples from Northern Sumatra namely Asahan, Tanjung Pura, Tanjung Balai, and Langsa. The method of sample selection was purposive random sampling.The hedonic test was performed by 30 panelists to differentiate the favored and unfavored shrimp pastes. Bacteria were isolated from Terasi with the highest score for taste and aroma using Nutrient Agar medium + 10% NaCl and several cultures were heated at 80 0 C for 15 min for isolated Bacillus spp. The shrimp pastes were tested for their chemical characteristics in percentage (%) e.g water content, carbohydrate, total fat, protein and salt content (NaCl). The hedonic test results showed that the shrimp paste originated from Langsa (Aceh) produced the highest score for taste (80.6%), aroma (81.1%) and the aroma of fresh shrimp paste (71.4%).The chemical characteristics of Northen Sumatra shrimp paste were, water content ranging from 29-34%, carbohydrate 0.89-2.91%, total fat 1.97-2.39%, protein 25-38%, and salt content 9.83-24%. Seven bacterial isolates were obtained from Langsa shrimp paste coded as IW1, IW2, IW3 and IW4 and three suspected Bacillus coded as B1, B2, and B3.